2004
DOI: 10.1007/s10350-003-0055-0
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Surgery With Accelerated Rehabilitation or Conventional Care

Abstract: Time to first defecation, hospital stay, and morbidity may be reduced after colonic resection with fast-track multimodal rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
288
8
30

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(344 citation statements)
references
References 24 publications
18
288
8
30
Order By: Relevance
“…The studies met with positive results. 5,6 Recently, a randomized controlled trial and a systematic review showed benefits of fast-track colorectal surgery. 7,8 In 2005, a team comprised of surgeons, anesthesiologists, nurses, physiotherapists, nutritionists, and epidemiologists of the McGill University Health Centre (MUHC) developed a multidisciplinary approach to colon resection with the intent to implement a fast-track program in this institution.…”
Section: Résumémentioning
confidence: 99%
“…The studies met with positive results. 5,6 Recently, a randomized controlled trial and a systematic review showed benefits of fast-track colorectal surgery. 7,8 In 2005, a team comprised of surgeons, anesthesiologists, nurses, physiotherapists, nutritionists, and epidemiologists of the McGill University Health Centre (MUHC) developed a multidisciplinary approach to colon resection with the intent to implement a fast-track program in this institution.…”
Section: Résumémentioning
confidence: 99%
“…78 One hundred thirty consecutive patients receiving conventional care (group 1) in one hospital were compared with 130 consecutive patients receiving multimodal fast-track rehabilitation (group 2) in another hospital. Outcomes were the time to first defecation after surgery, postoperative LOS, and morbidity during the first postoperative month.…”
Section: Multimodal Strategiesmentioning
confidence: 99%
“…e 3 o . dias pós-operatórios 33 . Essa prática diminui o desconforto dos doentes, o tempo de internação e conseqüentemente, os custos hospitalares.…”
Section: Correia Et Alunclassified